Planting density and supplementary irrigation on the response of three corn cultivars to water deficit in the "cerrados" region - Espinoza, Waldo; Azevedo, Juscelino; Rocha, Luiz A. (Pesquisa Agropecuaria Brasileira, 2014)
A study was conducted from 1976 through 1978, to evaluate the effect of supplementary irrigation and planting density (20.000 to 80.000 plants/ha) on the response of three corn cultivars: (Zea mays L.) Cargill -111X, Cargill 501 and Piranão, to natural or induced water deficits at critical plant stages. The data indicate that supplementary irrigation doubled yields, attaining 5 or 6 tons/ha, the most promising being the cultivar C-111x in population of 40.000 to 60.000 plants/ha. During rainfall period, best results were obtained again with the cultivar C-111x, with an optimun population, ranging from 20.000 to 40.000 plants/ha. Yield reductions due to drought were dependent on plant population and the extent of the drought period. Plant population seems to be a useful crop management practice to reduce the negative effect of drought periods of less than 25 days.